SENSITIVE LAYERS FOR OPTICAL SENSORY DEVICES FOR ALUMINUM - H.U., Usmanova; S, Bobozhonov H.; Z.A., Smanova (International Journal of Psychosocial Rehabilitation, 2020)
The possibility and optimal conditions for immobilization by eriochrome blue SE, eriochrome gray SQL on polymeric carriers were studied. The positive effect of immobilization of the investigated oxyazocompounds on their chemical-analytical properties is shown. The optimum conditions for the complexation of the reagents with aluminum are established. New systems of organic carrier reagent for solid-phase luminescent determination of aluminum are proposed.